Modernidade e(m) invenção: as gravuras de Johannes Stradanus (1523-1605) - Vespucci, Augusto Godinho (2021)
The Dutch printmaker, Johannes Stradanus (1523-1605) published, in the 1580s, two series of prints with the titles: “Nova Reperta” (ca. 1585) and “Americae Retectio” (ca.1588). These productions, for beyond of representations of the "New Inventions" and the "Discovery of America", are portraits of the European imagination of the late 16th century. Produced in Italy and published in the Netherlands, Johannes Stradanus' engravings sought to establish a new era based on the discourse of overcoming the Ancients. To analyze these recorded images, we started from an investigation of Stradanus' life, the market in which the series were produced and the historical context in which the author lived. In addition, we look at images and their intrinsic meanings as discourses, as well as in possible dialogues with images that shared the same signs and, therefore, the same Visual Culture.